2017
DOI: 10.1128/aem.03508-16
|View full text |Cite
|
Sign up to set email alerts
|

Metagenomic and Metatranscriptomic Analyses Reveal the Structure and Dynamics of a Dechlorinating Community Containing Dehalococcoides mccartyi and Corrinoid-Providing Microorganisms under Cobalamin-Limited Conditions

Abstract: The aim of this study is to obtain a systems-level understanding of the interactions between and corrinoid-supplying microorganisms by analyzing community structures and functional compositions, activities, and dynamics in trichloroethene (TCE)-dechlorinating enrichments. Metagenomes and metatranscriptomes of the dechlorinating enrichments with and without exogenous cobalamin were compared. Seven putative draft genomes were binned from the metagenomes. At an early stage (2 days), more transcripts of genes in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
16
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
2
1

Relationship

3
6

Authors

Journals

citations
Cited by 30 publications
(18 citation statements)
references
References 53 publications
2
16
0
Order By: Relevance
“…Dechlorinating cultures that grow in the absence of cobalamin have been reported before, yet incomplete dechlorination and VC accumulation occurred. 46,47 To our knowledge, this is the first report of complete and sustained dechlorination to ethene in dechlorinating mixed cultures grown without any exogenous vitamins.…”
Section: Dechlorination In Cell Extracts At Different Phmentioning
confidence: 83%
“…Dechlorinating cultures that grow in the absence of cobalamin have been reported before, yet incomplete dechlorination and VC accumulation occurred. 46,47 To our knowledge, this is the first report of complete and sustained dechlorination to ethene in dechlorinating mixed cultures grown without any exogenous vitamins.…”
Section: Dechlorination In Cell Extracts At Different Phmentioning
confidence: 83%
“…To exclude the bias of comparison of gene expression level caused by cellular growth, we normalized the number of mapped reads of a certain ORF against mapped reads of total ORFs from a certain genome for RPKM value calculation [48]. For instance, if gene a is present in genome A, the RPKM value will be calculated by the following equation:…”
Section: Methodsmentioning
confidence: 99%
“…A clone library analysis indicated that D. mccartyi species (57%) and Desulfovibrio species (22%) are the two dominant populations in culture EC195 (Table 1). Spirochaeta also occurred in culture EC195, which has commonly been found in other dechlorinating enrichment cultures (Men et al 2017;Kaufhold et al 2013).…”
Section: Chloroethene Dechlorination By An Autotrophic Culture Ec195mentioning
confidence: 65%